Reflexions about the distinction between Law and Gospel in the Lutheran Theology - Ogliari, Maycon Darci; Schwambach, Claus (Vox Scripturae - Revista Teológica Internacional, 2016)
This article intends to reflect the conceptualization and origin of the terms law and gospel in Lutheran theology, mainly from Luther’s own writings. It seeks to understand the origin of these terms and from which Luther was inspired to understand the dialectic between the law and the gospel. The law accuses and points out sin, and the gospel liberates from sin by pointing to the justifying work of Christ. Could the Old Testament be considered only law? Certainly not. According to Luther, the gospel was in the Old Testament already manifested in divine mercy and grace. But with the revelation of the New Testament would the law become unnecessary? Luther states that without the despair of the law, the Gospel would have no meaning and the understanding of Jesus’ sacrifice would be obsolete. The gospel is the power of God that set the sinner free from sin. Not by human merit, but by divine grace, by the unique work of Jesus Christ. According to Luther, the distinction between these terms is vital to characterize the true theologian, that is, one who knows how to discern and distinguish the law and the gospel in the preaching of the word of God. The distinction between law and gospel is fundamental in Lutheran theology, for it is this tension that transforms and impacts the human being, the despair of the law, and the sweet words of the gospel.